Competition on common value markets with naèive traders: a theoretical and experimental analysis - Nadine Chlaß; Werner Güth (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Theoretically and experimentally, we generalize the analysis of acquiring a company (Samuelson and Bazerman 1985) by allowing for competition of both, buyers and sellers. Naivety of both is related to the idea that higher prices exclude worse qualities. While competition of naive buyers increases prices, competition of naive sellers promotes effciency enhancing trade. Our predictions are tested experimentally.
Keywords: D01; D42; D43; D44; D61; D82; L13; L15; 330; Übernahme; Wettbewerb; Auktionstheorie; Unvollkommene Information; Test